Preparation of Iron Oxide and Titania-Based Composite, Core-Shell Populated, Nanoparticulates Material by Two-Step LASER Ablation in Aqueous Media as Antimicrobial and Anticancer Agents - Hasan H. Bahjat; Raid A. Ismail; Ghassan M. Sulaiman; Hamdoon A. Mohammed; Mohsen Al-Omar; Salman A. A. Mohammed; Riaz A. Khan (Bioinorganic Chemistry and Applications)
Iron oxide and titania-based composite nanoparticles (NPs) populated with core-shell structures, as part of the mixture of the monometallic NPs, were prepared in water medium by the two-fluence LASER ablation technique by applying 30 and 60 mJ/cm2 LASER energy irradiations. The prepared monometallics, composite, and core-shell NPs structures were confirmed from the XRD, TEM, and EDX analyses, followed by the FE-SEM and UV absorptions. Optically, the NPs exhibited an increase in the energy gap from 3.27 eV to 3.75 eV as LASER fluence increased from 30 mJ/cm2 to 60 mJ/cm2. The average NPs core size distributions for the core-shell material ranged at ∼70 nm with the shell thickness around 20 nm. The biggest NPs were of ∼170 nm size which were sparsely distributed. The magnetization behaviors of the NPs were also investigated using the vibrating sample magnetometer (VSM). The NPs showed antimicrobial activities against the pathogenic species: Escherichia coli and Staphylococcus aureus. The antimicrobial activities of the synthesized NPs, synthesized under the influence of magnetic fields, were found to be more potent than the NPs synthesized without the presence of any magnetic field. The NPs prepared under the influence of the magnetic fields also comparatively exhibited higher levels of cytotoxicity against lung cancer cell lines (A549) than the NPs prepared under no magnetic field’s influence by the similar energy level effects of the LASER fluence. The flow cytometry analyses confirmed the NPs’ cytotoxic impacts against the human lung cancer A549 cell lines through the initiation of apoptosis and promotion of the cell cycle arrest at the G1 phase of cell division. To further confirm the cytotoxic effects and the mechanism of the anticancer activity of the synthesized NPs against the A549 cell lines, several related parameters (cell viability, membrane permeability, nuclear intensity, and cytochrome-C release) were analyzed using the high-content screening (HCS) assay. The study suggested that the prepared NPs have potential as antimicrobial and also as anti-lung-cancer agents as tested in vitro. These NPs can also be part of combined chemotherapy in different oncological interventions, as well as a sonosensitizer in sonomagnetic heating-based therapy, especially for cancers.